Allegories of a poetic war: figures of authority in 17th century France - Sá, Luiz César de (Revista de História, 2022)
In 17th century France, the understanding that “quarrels” are the privileged mechanism for the institution of authority gains ground. Writings proposing gallant disputes, which praised verbal violence as opposed to the horrors of war, are vastly disseminated, giving birth to a specific genre. This article focuses on the analysis of the relations between authority and controversy formed by this genre based on the study of Nouvelle Allégorique (1658), a book that allegorizes the scholarly hostilities of its time with the main goal of archiving the very act of quarreling.